Forage Sorghum Performance Trial - J. L. Moyer; E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2015)
In our sorghum trials, production of forage was greater (P<0.05) for ‘FS 4’ and ‘AF 7401’ than for ‘AF 7202,’ possibly related to differences in maturity. Estimated grain production was greater for ‘AF 7401’ than for all others, except for ‘AF 7102.’
Keywords: forage sorghum hybrids; forage sorghum performance; East Central Kansas Experiment Field